2022
DOI: 10.1177/03635465221108972
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Exosomes and Ectosomes Isolated From Adipose-Derived Mesenchymal Stem Cells on Achilles Tendinopathy in a Rat Model

Abstract: Background: Extracellular vesicles derived from mesenchymal stem cells (MSC-EVs) have gained momentum as a treatment for tendinopathy. Multiple studies have demonstrated significant differences in cargo composition between the 2 subtypes of MSC-EVs (ie, exosomes and ectosomes), which may result in different therapeutic effects. However, the effects of the 2 EV subtypes on tendinopathy have not yet been compared. Purpose: To compare the effects of adipose stem cell–derived exosomes (ASC-Exos) and ectosomes (ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 46 publications
1
47
0
Order By: Relevance
“…In 2019, Chamberlain et al utilized exosome-educated macrophage–treated ATI exhibiting (a) improved mechanical properties, (b) reduced inflammation, and (c) earlier angiogenesis ( 32 ). Meanwhile, extracellular vesicles derived from mesenchymal stem cells have gained much momentum in the treatment of tendinopathies ( 33 ). Mesenchymal stem cells are a hot topic in the field of tendon regeneration engineering ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Chamberlain et al utilized exosome-educated macrophage–treated ATI exhibiting (a) improved mechanical properties, (b) reduced inflammation, and (c) earlier angiogenesis ( 32 ). Meanwhile, extracellular vesicles derived from mesenchymal stem cells have gained much momentum in the treatment of tendinopathies ( 33 ). Mesenchymal stem cells are a hot topic in the field of tendon regeneration engineering ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Animal Ethics Committee of the 2nd Affiliated Hospital, School of Medicine, Zhejiang University approved the animal research ethics. Isolation and culture of primary adipose-derived MSCs (ASCs) and chondrocytes from Sprague–Dawley rats were performed as we have described previously [ 21 , 22 ]. Briefly, minced adipose tissue was digested with 0.1% collagenase type I and cartilage particles were digested with 0.2% collagenase II at 37 °C for 4 h. Next, collected cells were seeded into 25-mm 2 culture flasks with corresponding mediums containing 10% fetal bovine serum (FBS).…”
Section: Methodsmentioning
confidence: 99%
“…Adipose-derived stem cells (ASCs) possess numerous desirable advantages, such as a less invasive collection process, high cellular yield, and great expansion capability [ 20 ]. In our prior study, we isolated exosomes and ectosomes from ASCs and analyzed their different micro-RNA expression profiles, though they partially overlap in size [ 21 ]. As we demonstrate, ASC-Exos have a stronger ability to inhibit inflammation than ASC-Ectos under the pathological condition of tendinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a rat model of Achilles tendonopathy found that MSC-derived EVs resulted in improved histological scores with improvements in collagen fibril diameter and superior biomechanical properties. 19 MSC-derived EVs have also been shown to improve ligament healing in a rat medial collateral ligament injury model, with increased expression of type 1 and type 3 collagen, improved collagen organization, and reduction in scar size. 3…”
Section: Tendon and Ligamentmentioning
confidence: 99%